U.S. CANADA SOFTWOOD LUMBER TRADE DISPUTES AND LUMBER PRICE VOLATILITY. - SHANG, DAOWEI ; CHANGYOU SUN
THIS PAPER USES ANALYSIS OF VARIANCE (ANOVA) ANDREGRESSION ANALYSIS TO STUDY U.S. SOFTWOOD LUMBERPRICE VOLATILITY BETWEEN 1980 AND 2000, THE PERIOD THAT COINCIDES WITH SEVERAL EPISODES OF U.S.-CANADA SOFTWOOD LUMBER TRADE DISPUTES. THE RESULTS SHOW THAT SOFTWOOD LUMBER PRICES WERE MORE VOLATILE IN THE 1990S THAN IN THE 1980S, WITH THE PERIOD BETWEEN 1991 TO 1996 BEING THE MOST VOLATILE...